2013
DOI: 10.1371/journal.pone.0079649
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis Optica in Austria in 2011: To Bridge the Gap between Neuroepidemiological Research and Practice in a Study Population of 8.4 Million People

Abstract: BackgroundIn 2008 the Austrian Task Force for Neuromyelitis Optica (NMO) started a nation-wide network for information exchange and multi-centre collaboration. Their aim was to detect all patients with NMO or NMO spectrum disorders (NMO-SD) in Austria and to analyse their disease courses and response to treatment.Methods(1) As of March 2008, 1957 serum samples (of 1557 patients) have been tested with an established cell based immunofluorescence aquaporin-4 antibody (AQP4-ab) assay with a high sensitivity and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
71
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 36 publications
6
71
5
2
Order By: Relevance
“…We found that a higher percentage of patients presenting with LETM had CSF pleocytosis when compared to the patients that presented with ON. Like in previous reports, brain MRI at disease onset was mostly normal or showed non-specific brain lesions [18][19][20]. With respect to spinal cord lesions, the results were also consistent with those of prior studies showing LETM in 52.5% of patients.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We found that a higher percentage of patients presenting with LETM had CSF pleocytosis when compared to the patients that presented with ON. Like in previous reports, brain MRI at disease onset was mostly normal or showed non-specific brain lesions [18][19][20]. With respect to spinal cord lesions, the results were also consistent with those of prior studies showing LETM in 52.5% of patients.…”
Section: Discussionsupporting
confidence: 91%
“…In spite of having found a higher percentage of patients with concomitant autoimmune disorders (15 patients, 22.4%) than it was reported in the French [16] (10.4%) and Hong Kong [18] (10.6%) studies, most of the encountered disorders were similar (mainly SLE and Sjogren's syndrome) except for the two cases of myasthenia gravis described in our cohort [13] and also in the Austrian one [20]. Since 66.7% of patients with autoimmune diseases had positive AQP4-IgG antibody, we hypothesize that its presence may be faced as an "autoimmune marker".…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations